UPAYA MENCEGAH PENYAKIT JANTUNG DENGAN OLAHRAGA - Fajar Ekawati1, Febriani (Pendidikan Dan Kepelatihan Olahraga, 2010)
Heart disease is one the main causes of the death in the world, the main factors causing this disease better known as the four factors for heart disease are hypertension, cholesterol, diabetes mellitus and smoking. Of the fourth factors, hypertension is a major cause for heart failure and stroke. Although heart disease becomes a major health problem in the world, but it can be prevented through healthy life style that is by doing endurance exercise. Exercise that can be done mainly aerobic or isotonic such as running, walking, low impact aerobics  etc, certainly it is better if going to do under doctor?s supervision.